When thyroid met brain: the enigma of steroid responsive encephalopathy associated with autoimmune thyroiditis a case report - Kotak, Palash; Khurana, Kashish; Raut, Sarang; Toshniwal, Saket Satyasham; Acharya, Sourya (Frontiers in Immunology, 2025)
Steroid Responsive Encephalopathy Associated with Autoimmune Thyroiditis (SREAT), or Hashimoto’s encephalopathy, is a rare autoimmune neurological disorder linked to elevated antithyroid antibodies and presenting various neurological symptoms. This report deals with a case of a 54-year-old female with a history of hypothyroidism who presented with hypertensive emergency and atypical neurological symptoms that deteriorated during the hospital stay. On testing, she was euthyroid. Initial investigations, including MRI and CSF analysis, were inconclusive, but high levels of antithyroid peroxidase (Anti TPO) antibodies confirmed the diagnosis of SREAT. The patient was managed with intravenous methylprednisolone, leading to rapid clinical improvement. SREAT, being a diagnosis of exclusion, presents with various neurological and neuropsychiatric symptoms that can be difficult to identify. This condition remains poorly understood, though autoimmune factors and antithyroid antibodies seem to play a role. Glucocorticoids remain the primary treatment choice. At the same time, other immunosuppressive agents are reserved for non-responders. This case highlights the critical importance of early diagnosis in SREAT, as early recognition and corticosteroid treatment can lead to significant recovery. Timely intervention is essential for improved patient prognosis, emphasizing the need for awareness of SREAT in patients with a history of hypothyroidism presenting with neurological symptoms.